Pendidikan Kesehatan Gigi dan Mulut Serta Protokol Kesehatan di Masa Pandemi Pada Guru PAUD Aldercy Surakarta - Widia Susanti; Risya Cilmiaty A. R; Betty Saptiwi; Adi Prayitno; Pradipto Subiyantoro; Filumena T. R (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Aldercy Early Childhood Education (PAUD) is a kindergarten located in Kadipiro, Banjarsari, Surakarta City, Central Java. During the pandemic, students must be able to implement health protocols and maintain dental and oral health by brushing their teeth properly. PAUD teachers can become cadres for their students to provide education and training on those issues. The purpose of this activity is to carry out one of the components of the Tri Dharma of Higher Education, namely community service. The benefits of this activity are forming cadres, namely Aldercy PAUD teachers, so they can provide education about health protocols during a pandemic and dental and oral health for students at Aldercy PAUD. The method of service is lectures and training on health protocols during a pandemic and dental and oral health. The target audience was 12 Aldercy PAUD teachers. The results showed that this activities ran smoothly and participants were enthusiastic. Aldercy The participants were also trained to become dental and oral health cadres. The participants are expected to provide education regarding oral health protocols to their students, as well as maintain the program by supervising and fostering health protocols during the pandemic and maintaining oral and dental health.